Carcinoma of the fallopian - Valdivia Ponce, Eduardo (2015)
The primary carcinoma of the tube is a rare neoplasm. At the National Institute of Neoplastic Diseases in the last four years it has an incidence of 0.12 percent among all malignancies pelvic genital tract. The clinical symptoms are not typical. The diagnosis has been a surgical and pathology findings. The cytodiagnosis by the method of the three sheets, completed its examination of the biopsies, help you think about the possibility of carcinoma of the tube. In our case, one of adeno-carcinoma well differentiated papilliferum, is alive and in good condition; two of anaplastic type, showed recurrence within a few months and ended up dying at 6 and 7 months, respectively. You may histologic type is related to prognosis. The treatment is subject to the stage of evolution. It should be as radical as possible. Often it is complemented by X-ray and chemotherapy.